Penerapan Praktikum Berbasis Lingkungan untuk Meningkatkan Pemahaman Konsep Spermatophyta di SMP Negeri 4 Manado - Tesalonika Yohana Wowat; Arrijani Arrijani; Meity N. Tanor (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This study aims to analyze student activities and learning outcomes in the learning of Spermatophyta sub-material through practicum activities based on Exploring the Environment at SMP Negeri 4 Manado. The background of this study is based on the need for a contextual approach to biology learning and being able to increase student engagement actively. The method used was quantitative descriptive research with survey techniques, involving 20 grade VII students and 2 science teachers as respondents. The research instrument consisted of a closed questionnaire, an open interview, and an observation sheet. The questionnaire results showed that students responded very well to this learning method, with an average score of 83.4%. At the same time, teachers rated this approach as effective, with an average of 88%. Observations showed that students were active in practicum activities, enthusiastic in making observations, and involved in group discussions. The interview revealed that this environment-based learning strengthens students' understanding of biological concepts and increases scientific curiosity. The obstacles found include the accuracy of recording and the inequality of roles in group work. However, overall, exploring the Surroundings-based learning has been proven to positively impact student engagement and understanding, especially in connecting theory with real objects in the surrounding environment. The implications of this study emphasize the importance of applying contextual approaches in biology learning and suggest improving guidance strategies and recording of observations in the field for more optimal learning effectiveness.